Left atrioventricular coupling index to predict incident heart failure: the multi-ethnic study of atherosclerosis (MESA). (13th July 2021) - Pezel, T; Ambale Venkatesh, B; Kato, Y; De Vasconcellos, H; Heckbert, S; Wu, C; Post, W; Bluemke, D; Cohen Solal, A; Henry, P; Lima, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Although left atrial (LA) and left ventricular (LV) structural and functional parameters have independent prognostic value as predictors of HF, the close physiological relationship between LA and LV suggest that the assessment of LA/LV coupling could better reflect left atrioventricular dysfunction and be a better predictor of heart failure (HF). PURPOSE: We investigated the prognostic value of a left atrioventricular coupling index (LACI), measured by cardiovascular magnetic resonance (CMR), as well as change in LACI to predict incident HF in the Multi-Ethnic Study of Atherosclerosis (MESA). METHODS: In the MESA, 2, 250 study participants, free of clinically recognized HF and cardiovascular disease at baseline, had LACI assessed by CMR imaging at baseline (Exam 1, 2000–2002), and ten years later (Exam 5, 2010–2012). LACI was defined as the ratio of LA to LV end-diastolic volumes. Univariable and multivariable Cox proportional hazard models were used to evaluate the associations of LACI and average annualized change in LACI (ΔLACI) with incident HF after adjustment on traditional HF risk factors. The incremental risk prediction was calculated using C-statistic, categorical net reclassification index (NRI) and integrative discrimination index (IDI). RESULTS: Among the 2, 250 participants (mean age 59.3 ± 9.3 years and 47.6% male participants), 50 incident HF events occurred over 6.8 ± 1.3 years after the second CMR exam. After adjustment, greater LACI and ΔLACI were independently associated with HF (adjusted HR 1.44, 95% CI [1.25-1.66] and adjusted HR 1.55, 95% CI [1.30-1.85], respectively; both p < 0.0001). Adjusted models for LACI showed significant improvement in model discrimination and reclassification compared to currently used HF risk score model for predicting HF incidence (C-statistic: 0.81 vs. 0.77; NRI = 0.411; IDI = 0.043). After adjustment, ΔLACI showed also significant improvement in model discrimination compared to the multivariable model with traditional HF risk factors for predicting incident HF (C-statistic: 0.82 vs. 0.77; NRI = 0.491; IDI = 0.058). CONCLUSIONS: In a multi-ethnic population, atrioventricular coupling (LACI) and coupling change (ΔLACI) are independently associated with incident HF. Both have incremental prognostic value for predicting HF over traditional HF risk factors.